Risky medicine our quest to cure fear and uncertainty - Aronowitz, Robert A. (The University of Chicago Press, 2015)
Drawing on such controversial examples as HPV vaccines, cancer screening programs, and the cancer survivorship movement, Aronowitz demonstrates that patients and their doctors have come to believe, perilously, that far too many medical interventions are worthwhile because they promise to control our fears and reduce uncertainty.